“DEVELOPMENT OF CREATIVE THINKING – DETERMINES THE QUALITY OF EFFECTIVE EDUCATION” - Raikhan Bazarbayeva (Western European Studies, 2024)
The formation of qualities such as thought, imagination, creativity in a student, the enrichment of his creative world is a step-by-step process, in which the personality of the teacher plays a very special role. This article will focus on the development of the student's creative abilities.
Keywords: creativity; imagination; creative task; development of creative abilities